2007
DOI: 10.1038/sj.bjc.6603907
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CC chemokine receptor 7 in tonsillar cancer predicts cervical nodal metastasis, systemic relapse and survival

Abstract: The aim of this study was to evaluate the expression of CC chemokine receptor 7 (CCR7) in squamous cell cancer of the tonsil with respect to patterns of spread, relapse-free, overall and disease-specific survival. Eighty-four patients with squamous cell cancer of the tonsil were identified. There was a male predominance of 3 : 1 and the median age at diagnosis was 53 (range 35 -86) years. The median duration of follow-up was 33 (range 2 -124) months. There was a significant association between CCR7 immunoposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 15 publications
(14 reference statements)
0
23
0
Order By: Relevance
“…Overexpression of CCR7 in B16 melanoma cells has been shown to not only result in increased LN metastasis [38] but also contribute directly to melanoma cell tumorigenesis [39]. As with CXCR4 expression [40], CCR7 expression by human cancers has been correlated with poor patient outcome, which is consistent with a large array of data that links nodal metastasis with poor patient survival in most cancers, including melanoma [13,41,42]. Some breast cancer cell lines were reported to have elevated CXCR3, which also increased the incidence of lung metastasis [15].…”
Section: Cancer Cells Alter Chemokine and Ckr Expressionmentioning
confidence: 64%
“…Overexpression of CCR7 in B16 melanoma cells has been shown to not only result in increased LN metastasis [38] but also contribute directly to melanoma cell tumorigenesis [39]. As with CXCR4 expression [40], CCR7 expression by human cancers has been correlated with poor patient outcome, which is consistent with a large array of data that links nodal metastasis with poor patient survival in most cancers, including melanoma [13,41,42]. Some breast cancer cell lines were reported to have elevated CXCR3, which also increased the incidence of lung metastasis [15].…”
Section: Cancer Cells Alter Chemokine and Ckr Expressionmentioning
confidence: 64%
“…Furthermore, FoxP3 binds to the gene region upstream of the transcriptional start site of CCR7 and CXCR4 [97], two chemokine receptors recently reported to play an important role in cancer invasion and metastasis [98,99]. Thus, FoxP3 expressed in breast cancer cells might influence metastasis development by modulating the expression of these chemokine receptors or of other genes encoding cell surface or secreted molecules that alter tumor cell response to the environment [80].…”
Section: Possible Functions Of the T Cells In Disseminated Breast Cancermentioning
confidence: 96%
“…In a recent study, a strong association was reported between CCR7 expression and synchronous nodal metastasis in patients with tonsillar cancer. [80] Only 1 of 11 (9.1%) patients with a negative CCR7 immunohistochemistry had nodal involvement at presentation, in contrast to 8 of 13 (61.5%) patients with "+" staining, 24 of 27 (88.9%) patients with "++" staining, and 29 of 33 (87.8%) patients with "+++" staining. Similarly, the degree of CCR7 immunopositivity was directly correlated with the extent of nodal metastasis at diagnosis, such that 43 of 44 (97.7%) patients with N2 or N3 disease had "++" or "+++" immunostaining at diagnosis.…”
Section: Targeting Invasion and Metastasismentioning
confidence: 65%